The biochemistry of inorganic polyphosphates - Kulaev, I. S. (Igorʹ Stepanovich) (J. Wiley, 2004)
Now in a second edition, Biochemistry of Inorganic Polyphosphates fills the need for an exhaustive resource on inorganic polyphosphate metabolism. The authors describe the structure and properties of these compounds and presents a comparative analysis of the newest and traditional methods of their extraction from cells. Distribution of polyphosphates in organisms, their localization in cells and tissues is also described.: Comprehensive presentation of inorganic polyphosphate metabolism; Follows polyphosphates in cells of organisms from different stages of evolution; Presents methods for the a.